Development of Allelopathic rice genotype with high grain zinc content through marker-assisted backcross - Mazid, Muhammad Sirajul (2018)
Rice cultivation is hindered by biotic and abiotic stresses. Among the biotic stresses, weeds like barnyard grass can cause significant reduction of rice yield. The efficacious approach to control barnyard grass is by using allelopathic rice genotype integration management with minimum chemical control method. Zinc (Zn) deficiency is one of the critical problems of global malnutrition for humans. The problem affected approximately half of the world’s population. The genetic biofortification together with agronomic biofortification of staple food crop is considered the most effective approach to prevent Zn deficiency. Marker-assisted selection (MAS) can potentially hasten breeding programs for varietal development. Marker-assisted backcrossing (MABC) is one of the most-useful ways of transferring specific gene(s) or QTL(s) into a popular variety. In this study, high grain Zn QTLs were transferred from an indica rice donor BRRI dhan62, using MABC method, into an allelopathic elite indica rice variety, MR73 to develop one superior genotype which has both allelopathic trait along with high grain Zn. Twenty eight microsatellite markers linked to the Zn QTLs or grain Zn content were selected and used in this study to determine potential association with Zn QTLs. These polymorphic foreground markers were used for confirmation of Zn QTLs or presence of grain Zn content gene in the F1 population. Subsequently, only three microsatellite markers, RM152, RM3331 and RM3909 that indicated Zn QTLs located on chromosomes 8, 12 and 9 respectively, were used on BC1F1, BC2F1 and BC2F2 populations. Out of 405 microsatellite markers, 75 were found to have polymorphism between parental varieties and were used for recurrent parent genome recovery (RPG) analysis in each generation. Chi-square analyses of foreground markers showed an expected segregation ratio of 1:1 in BC1F1 and BC2F1 generations indicating inheritance in simple Mendelian fashion. This result confirmed that grain Zn content trait in BRRI dhan62 is governed by single dominant gene. The genotypic segregation of BC2F2 population applying RM152, RM3331 and RM3909 exhibited 1:2:1 ratio. Results confirmed that single dominant gene control high grain Zn in BRRI dhan62 located on chromosomes 8, 12 and 9 are linked to RM152, RM3331 and RM3909 markers respectively. The RPG analysis of the improved genotypes indicated recurrent parent genome recovery ranging from 70.20-91.40% in BC1F1 generation, 80.50-93.00% in BC2F1 and 93.10-95.40% in BC2F2. The average RPG in BC2F2 selected improved genotypes were 93.86%, explaining the very close similarity at phenotypic level with the recipient parental variety MR73. Ten homozygous dominant Zn QTLs plants which are phenotypically closely similar for agro-morphological traits to MR73 were selected as improved high grain Zn breeding genotypes. The agronomic traits showed no significant difference between MR73 parent and Zn QTLs containing MR73 improved genotypes except the trait days to 50% flowering. Moreover, average Zn content in brown rice of improved genotypes was 40 mg kg-1 which was higher than the recurrent parent MR73 (27.99 mg kg-1). Furthermore, the ability of newly improved rice genotypes to suppress the growth of barnyard grass which is expressed through average percent inhibition was 39.98%. The improved rice genotypes including these research findings could be used as valuable source for further high grain Zn rice breeding programmes in future.